Interpersonal Psychotherapy Adapted for the Group Setting in the Treatment of Postpartum Depression - Klier, Claudia M. (American Psychiatric Press, Inc, 2001)
Interpersonal psychotherapy (IPT) has demonstrated efficacy in the individual treatment of antepartum and postpartum depression. The current investigation extends prior work by examining the efficacy of a group IPT approach for the treatment of postpartum depression. Depression scores of 17 women diagnosed with postpartum depressive disorder (DSM-IV criteria) decreased significantly from pre- to post-treatment. Follow-up assessments at 6 months revealed continuation of the treatment effect. Results indicate that IPT adapted for a group model has positive implications for the treatment of postpartum depression, demonstrating both short-term and longer-term effects in the reduction of depressive symptomatology. Study limitations include the small sample size, absence of control group, possible bias in therapist's assessments, and lack of monitoring adherence, which may have jeopardized the accuracy of the results.